Perancangan Usaha Pengolahan Ikan Nila Presto - Budi Lukman Hakim; Encep Jianul Hayat; Dede Setiawan (Institut Teknologi Garut, 2023)
Company planning is an activity that can provide guidance in running a company, as well as identifying opportunities and analyzing and evaluating things that affect the company's targets. The company's design focuses on planning technical aspects, carrying out production trials to ensure product efficiency and quality by using a combination of experimental design methods and the BORDA method, as well as describing production flow mapping with operation process maps (PPO). Marketing aspects include market analysis and segmenting, targeting and positioning. Aspects of business organization and human resource needs are also taken into account. Apart from that, legal aspects and environmental aspects are also evaluated based on government regulations. Meanwhile, a feasibility study is an assessment process carried out to determine whether a project, business or activity has the capability and is feasible to implement. The feasibility study reviews financial analysis that shows profitable potential in the business, with positive feasibility indicators in cash flow calculations, a payback period of 7 months 16 days, a positive Net Present Value (NPV), and an Internal Rate of Return (IRR) of 9.06%, exceeding MARR value is 5.75%. So the design of the presto tilapia fish business is feasible.